К ЦИКЛУ РАЗВИТИЯ ТРЕМАТОДЫ BUCEPHALUS MARINUM В РЫБАХ ЧЕРНОГО МОРЯ - (:unkn) unknown (Киев : Наукова думка, 1985)
Экспериментальным путем подтверждена видовая принадлежность метацеркарии Bucephalus marinum — массового паразита морских собачек. Установлено, что длительность развития этого гельминта от метацеркарии до половозрелой мариты при температуре воды 19—23 °С составляет 20—25 дней. Дана морфометрия трематод на разных стадиях развития.
To development cycle of Bucephalus marinum trematodes in fishes of the Black Sea
Experiments are reported on rearing Bucephalus marinum up to marita sexual maturity. Periods of Bucephalus marinum development are established (20—25 days at water temperature 19—23 °C). Drawings and morphometric measurements of trematodes are presented for different developmental stages. Species belonging of Bucephalus marinum is confirmed.